Improving mechanical properties of recycled fibre-reinforced concrete through the use of magnetic water - Mahdi Jangi; Amin Honarbakhsh; Davoud Tavakoli (Advances in Civil and Architectural Engineering, 2025)
This study investigated the performance of Polyethylene terephthalate (PET), polypropylene, and steel fibres in concrete, utilizing both regular and magnetic water. The primary objectives were to explore the effect of magnetic water on the mechanical properties of fibre-reinforced concrete and to compare the performance of these fibres under identical conditions. Fibres were incorporated at dosages of 1-3 % by volume in concrete prepared with two different water types: regular and magnetic. Tests, including compressive strength, flexural strength, water permeability, and Young’s modulus, were conducted on the samples. The results indicated that steel fibres outperformed the other fibre types in terms of overall performance, with the highest compressive strength observed in samples containing 3 % steel fibres. Specifically, among the samples utilizing regular water, the increase in compressive strength compared with the control was approximately 25 %, whereas for samples incorporating magnetic water, the increase was 23 %. In contrast, polypropylene fibres caused a 14 % reduction in compressive strength in both regular and magnetic water samples, whereas PET fibres exhibited similar compressive strength to that of the control sample. Magnetic water demonstrated a positive effect on all concrete properties and improved the microstructure by reducing pore content. Notably, the compressive strengths for samples with magnetic water increased by about 10 % across all fibre types compared with regular water. However, no significant difference in the performance of fibre-reinforced concrete was observed between magnetic and regular water beyond this increase.